Abordagem da Violência contra a Mulher no Ensino Médico: um Relato de Experiência - Machado, Dinair Ferreira; Mclellan, Kátia Cristina Portero; Murta-nascimento, Cristiane; Castanheira, Elen Rose Lodeiro; Almeida, Margareth Aparecida Santini De (Associação Brasileira de Educação Médica, 2016)
ABSTRACT The following article is an experience report on the incorporation of the theme of violence against women in the medical curriculum. The objectives of this study were to describe the theoretical framework of the theme of violence against women and to identify the learning activities acquired by students. The module activities were developed throughout 10 weekly meetings with groups of 12 students, and are as follows: (a) read a study case of a woman in a violent situation and perform a literature review; (b) conduct visits to Primary Health Care Services and a Specialized Reference Center for Social Assistance; (c) systematize theoretical and practical data for strategic planning; and (d) present the activities developed to other student groups. At the end of the module, four relevant learning activities were identified in terms of women’s health: (a) the influence of socio-cultural and psychosocial phenomena in the health-disease process; (b) the importance of comprehensive care; (c) the Family Health Strategy as a facilitator in detecting and monitoring cases; and (d) violence against women as a relevant public health problem in the medical curriculum and training.

RESUMO Trata-se de um relato de experiência sobre a incorporação do tema da violência contra a mulher no ensino médico. O objetivo do estudo foi descrever as correntes teóricas explicativas da violência contra a mulher e as formas de intervenção apreendidas pelos estudantes. Foram realizados dez encontros semanais com um grupo de 12 estudantes e desenvolvidas as seguintes atividades: (a) leitura de um caso de uma mulher em situação de violência, busca na literatura científica; (b) visitas a serviços de atenção primária à saúde e ao Centro de Referência Especializado de Assistência Social; (c) sistematização dos dados teóricos e práticos para construção do planejamento estratégico; (d) apresentação das atividades realizadas aos demais grupos de alunos. Ao final do módulo, destacou-se o aprendizado de quatro aspectos importantes das implicações do tema para a saúde das mulheres: (a) influência dos fenômenos socioculturais e psicossociais no processo saúde-doença; (b) importância da integralidade no atendimento; (c) a estratégia de saúde da família como facilitadora na detecção e acompanhamento dos casos; (d) violência contra a mulher como um problema de saúde pública pertinente na formação médica.
Addressing Violence against Women in Medical Education: an Experience Report
Keywords: Violence against Women; Medical Curriculum; Problem-Based Learning; Violência contra a Mulher; Educação Médica; Aprendizado Baseado em Problemas